Isolation and characterization of deteriorated sectors from duplicate strain A of A. nidulans. - L. Favraud; J. L. Azevedo (Fungal Genetics Reports, 1987)
Isolation and characterization of deteriorated sectors from duplicate strain A of A. nidulans.